Pelatihan Komunikasi Bisnis dengan Metode Komunikasi Tertulis dan Lisan pada Pembangunan Bisnis Masyarakat Kota Surabaya - Novita Nurul Hayah (Fakultas Dakwah IAIN Jember, 2022)
The business world is a competitive world. Business also makes communication very important in it. Such is the case when managers contact subordinate employees or their clients, governments or tax service companies. Communication must be studied carefully, both for those who send messages and those who receive messages. Communication can be done by means of communication through written media, electronic media, and voice media. The method of implementing the activity is a form of socialization using a two-way interactive method, namely the way of providing socialization is done by providing information from students and lecturers explaining the material using power points, giving training leaflets directly to the community. In planning, the intent or purpose of delivering business messages must be determined in advance, both in general and in particular. Another step in the business message planning process is determining the main idea. The main idea is a summary of the messages conveyed. By determining the main idea will be obtained direction or instructions on what to do. Then it is also necessary to select the communication channel that will be used, both oral communication and written communication. Business messages can create added value for the company. Messages conveyed to other parties should be able to maintain and improve the company's image. To be able to create good will, every business message should have a clear goal, can be measured, and do not conflict with the goals of the organization.